The Relationship of Knowledge and Attitudes of Housewives about Sexually Transmitted Diseases with IVA Examination at the Tanjung Morawa Health Center - Ermita Silvana Putri Simanungkalit (International Archives of Medical Sciences and Public Health, 2022)
Health is a gift that needs to be considered and maintained throughout life. Health improvement can be done by maintaining a lifestyle. The purpose of this study was to determine the relationship between knowledge and attitudes of housewives about sexually transmitted diseases with VIA examination at Tanjung Morawa Health Center. This type of research is an analytic survey with a cross sectional approach. The total population in this study were housewives at the Tanjung Morawa Health Center. By taking the sample using the accidental sampling technique, the sample is carried out by taking respondents who happen to exist or are available in a place according to the research context as many as 30 people. The test used is by using the Chi-Square test. From the results of the study, the results of the Chi Square cross tabulation of the relationship between knowledge and IVA examination were 0.000, where 0.000 < 0.05, the Chi Square results in the cross tabulation of the relationship between mother's attitude and IVA examination was 0.000, where 0.000 < 0.05 so that there was a relationship between knowledge and mother's attitude. with VIA examination. The conclusion of this research is that there is a relationship between knowledge and attitudes of housewives about sexually transmitted diseases with VIA examination at the Tanjung Morawa Health Center. So that it can be suggested to health workers to provide counseling about PMS more often to the community and can encourage mothers in the Tanjung Morawa Health Center work area to be more active in participating in every counseling.